The role of profit sharing in dual labour markets with flexible outsourcing - Erkki Koskela; Jan König (Institute for the Study of Labor (IZA), 2011)
We combine profit sharing for high-skilled workers and outsourcing of low-skilled tasks in partly imperfect dual domestic labour markets, when the wage rate for low-skilled worker is set by a labor union, to analyze how the implementation of profit sharing influence flexible outsourcing and low-skilled labour market outcome. Profit sharing has a positive effect on the low-skilled wage and thus an outsourcing enhancing character. Profit sharing for high-skilled workers increases the low-skilled wage and helps to decrease the wage dispersion. Concerning the employment effects there is an employment reducing effect due to higher low-skilled wage, which can be offset by the employment increasing effect of higher effort of the high-skilled worker. Therefore, the employment effects of profit sharing are ambiguous.
urn:nbn:de:101:1-2011062853
Keywords: J31; J33; J51; 330; flexible outsourcing; profit sharing; dual labour market; employee effort